Three new species and new records in the wolf spider subfamily Sosipinae from Argentina (Araneae: Lycosidae) - Piacentini, Luis Norberto (2011)
Three new species of Sosippinae from Argentina are described; one new species of Hippasella Mello-Leitão, 1944, H. alhue sp. nov., from temperate Andean forests in the Argentinean provinces of Neuquén and Río Negro and two new species of Aglaoctenus Tullgren, 1905, A. yacytata sp. nov., from the rainforests in Misiones province, and A. puyen sp. nov., from temperate Andean forests in Río Negro province. Aglaoctenus oblongus (C. L. Koch, 1847) is recorded for first time in Entre Ríos province and new records for Buenos Aires province (Argentina) and Montevideo (Uruguay) are provided. The distribution of A. lagotis (Holmberg, 1876) is updated with first time records for the Argentinean provinces of Jujuy, Salta, Chaco, Formosa, La Rioja, Tucumán, Santiago del Estero, San Luis and Entre Ríos, new localities in the provinces of Misiones, Corrientes, Santa Fé and Córdoba.